2019
DOI: 10.1371/journal.pone.0217656
|View full text |Cite
|
Sign up to set email alerts
|

Determination of iris thickness development in children using swept-source anterior-segment optical coherence tomography

Abstract: Purpose The uvea comprises the iris, ciliary body, and choroid. However, the development of the anterior part (iris and ciliary body) in children is not yet fully elucidated. We investigated the iris thickness (IT) in children using swept-source anterior-segment optical coherence tomography (ASOCT). Methods In this retrospective, clinic-based study, we enrolled 41 children (mean ± standard deviation: 6.8 ± 3.3 years; range: 3–16; 17 males) with normal or mild refractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Additionally, we have previously reported that temporal mean iris thickness values in children (3-16 years) at 1 and 2 mm were 0.405 and 0.336 mm, respectively. In the nasal angle area, the mean iris thickness values were 0.459 and 0.338 mm, respectively [11], which also supports the thicker iris in the left eye. Therefore, the anterior chamber of the left eye became more cramped compared to the right eye.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, we have previously reported that temporal mean iris thickness values in children (3-16 years) at 1 and 2 mm were 0.405 and 0.336 mm, respectively. In the nasal angle area, the mean iris thickness values were 0.459 and 0.338 mm, respectively [11], which also supports the thicker iris in the left eye. Therefore, the anterior chamber of the left eye became more cramped compared to the right eye.…”
Section: Discussionsupporting
confidence: 62%
“…The scleral spur anatomically represents the junction between the inner wall of the trabecular meshwork and the sclera and is marked by a prominent inner extension (inward protrusion) of the sclera with a change in curvature of its inner surface [ 13 ]. This was identified in this study based on Nakakura et al [ 14 ].…”
Section: Methodsmentioning
confidence: 78%
“…Children have a low IT because their iris has not yet developed completely. 25,26 Older adults may have a lowest IT due to age-related degeneration of the iris. The three layers of the iris were affected to different degrees, and histological studies should be conducted to investigate this.…”
Section: Resultsmentioning
confidence: 99%